THE PREPAREDNESS FOR THE COVID-19 PANDEMIC MANAGEMENT IN INDONESIA - Muchammad Iqbal Firmansyah; Fajar Rahmanto; Deni Setiawan (Indonesian Journal of Health Administration, 2020)
Background: The increase in disaster events requires preparedness from health workers as the frontline to provide medical services in handling victims when a disaster occurs. Many of medical workers infected with COVID-19 where at least 47 nurses in Indonesia have tested positive with the number of nurses having ODP and PDP status totaling 546 people and 44 people cause additional problem in handling COVID-19.Aims: This article aims to determine the readiness of health workers in handling pandemic disasters in suppressing the potential risks due to the COVID-19 outbreak through medical services provided.Methods: The research method used is descriptive qualitative with a literature study approach. Secondary data collection techniques from previous references and public documents related to COVID-19 disaster management in Indonesia. Data analysis using NVivo12 Plus software with a query analysis approach.Results: The results showed the ratio of health workers in Indonesia for medical services in handling the COVID-19 pandemic disaster was not ideal were for doctors 0.4 and nurses 2.1 were still far behind from developed countries where the ratio of health workers was above 2.5 doctors and 5.5 for nurses. Then, infrastructure aspects in general for referral hospitals handling COVID-19 almost in every province that has supported through the distribution of medical material equipment to various regions, provinces and districts, as well as hospitals that need it in all areas of Indonesia in the form of surgical masks (1,997,684 pieces), PPE of 1,659,955 units, coupled with Rapid Test equipment of 1,011,130 units.Conclusion: The readiness of health workers in providing medical services for the handling of a pandemic disaster influenced by the number of human resources, operational standards, and facilities for health facilities.Keywords: health workers, medical services, pandemic disaster management, COVID-19